2020
DOI: 10.1111/1758-2229.12847
|View full text |Cite
|
Sign up to set email alerts
|

A hydrogen‐oxidizing bacterium enriched from the open ocean resembling a symbiont

Abstract: A new autotrophic hydrogen-oxidizing Chromatiaceae bacterium, namely bacterium CTD079, was enriched from a water column sample at 1500 m water depth in the southern Pacific Ocean. Based on the phylogeny of 16S rRNA genes, it was closely related to a scaly snail endosymbiont (99.2% DNA sequence identity) whose host so far is only known to colonize hydrothermal vents along the Indian ridge. The average nucleotide identity between the genomes of CTD079 and the snail endosymbiont was 91%. The observed differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 86 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…Although the evidence of free-living symbiont populations of scaly-foot snails in the environment is currently unavailable, the symbiont possesses highly similar genomic features, central metabolic pathways, and motility (i.e. flagellar genes and chemotaxis genes) to its closest known freeliving relative, the Chromatiaceae bacterium CTD079 [35]. The symbionts of scaly-foot snails from the five vents possessed assembly sizes ranging from 2.52 to 2.83 Mb (Table S1), including a genome size of 2.60 Mb as reported by Nakagawa et al 2014, close to that of the Chromatiaceae bacterium CTD079 (genome size: 2.75 Mb).…”
Section: Results and Discussion Transmission Modementioning
confidence: 99%
See 2 more Smart Citations
“…Although the evidence of free-living symbiont populations of scaly-foot snails in the environment is currently unavailable, the symbiont possesses highly similar genomic features, central metabolic pathways, and motility (i.e. flagellar genes and chemotaxis genes) to its closest known freeliving relative, the Chromatiaceae bacterium CTD079 [35]. The symbionts of scaly-foot snails from the five vents possessed assembly sizes ranging from 2.52 to 2.83 Mb (Table S1), including a genome size of 2.60 Mb as reported by Nakagawa et al 2014, close to that of the Chromatiaceae bacterium CTD079 (genome size: 2.75 Mb).…”
Section: Results and Discussion Transmission Modementioning
confidence: 99%
“…b Phylogenetic tree based on 1499 single-copy core genes of scaly-foot snail endosymbionts from the five vent fields. The Chromatiaceae bacterium CTD079 served as an outgroup (Sass et al 2020 [ 35 ]). c Phylogenetic tree of host scaly-foot snails based on 11 protein-coding genes of the mitochondrial genome from the five vent fields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Adam et al, 2021 ), single cell separation micro tweezer technologies ( Fröhlich and König, 2000 ; cf. Sass et al, 2020 ), flow cytometry ( Ferrari et al, 2012 ), diffuse chamber incubation ( Kaeberlein et al, 2002 ) etc. These approaches have resulted in the description of some hundred microbial species with hydrothermal origin ( Jebbar et al, 2015 ).…”
Section: The Not Yet Cultivated Microbial Majority and Its Potential ...mentioning
confidence: 99%
“…Previously, the chemoautotrophic Candidatus Thiobios was thought to be unable to survive without its symbionts (Bauer-Nebelsick et al, 1996). However, an autotrophic Chromatiaceae bacterium was found to exist in the water column at 1500 m water depth in the southern Pacific Ocean, based on the phylogenetic analysis of 16S rRNA genes, this bacterium was closely related to the endosymbiont of scaly snails, and showed similar functionality (Sass et al, 2020). Furthermore, cultivation experiments of the thiotrophic symbiosis between Zoothamnium niveum and Candidatus Thiobios zoothamnicoli showed that the symbiosis was not able to survive without sulfide.…”
Section: Characterize the Microbial Communities Of Scaly-foot Snails From Kairei And Longqi Vent Fieldsmentioning
confidence: 99%